Recontouring teeth and closing diastemas with direct composite buildups: a 5-year follow-up - Frese, Cornelia; Schiller, Petra; Staehle, Hans Jörg; Wolff, Diana (Journal of dentistry, 2013)
Objectives - Adhesive resin composite technology enables dentists to add composite material to tooth surfaces to close gaps and reshape tooth form without cavity preparation. This option creates new possibilities for minimally invasive dentistry as the tooth shape, position and colour can be altered without loss of tooth substance. However, evidence-based data on direct composite buildups are rare. - Methods - The purpose of this study was to evaluate the outcome and to document the occurrence of unfavourable events and clinical findings of 176 direct composite buildups that had been performed in the Department of Conservative Dentistry, University Hospital Heidelberg, Germany, between 2002 and 2008. Outcome was categorised as failure (F), survival (SR) or success (S). Restorations still in place and without prior failure at follow-up were qualitatively rated using modified USPHS/FDI criteria. - Results - During the follow-up period, 30 restorations were found to have had unfavourable events or clinical findings. All restorations were repaired, and they remained in situ (SR). No complete loss (F) was recorded. The overall survival rate was 84.6% after 60 months (95%, confidence interval [CI]: 78.5 and 90.6). Clinical quality was rated excellent or good for most (>90%) of the restorations examined. - Conclusions - The direct composite buildups observed in this study were found to have promising clinical outcome and good quality parameters after 5 years. If a noninvasive or minimally invasive treatment approach is indicated, direct composite buildups provide an acceptable treatment alternative for the aesthetic correction and reshaping of anterior teeth. - Clinical significance - The application of direct composite buildups in clinical cases in which a non- or minimally invasive treatment approach is indicated provides an excellent treatment alternative for gold-standard treatment options like laboratory-made crowns and porcelain veneers. Restorations in the present investigation showed a functional survival rate of 100%, an overall survival rate of 84.6% after 5 years.
Gesehen am 17.05.2021